Optimal geometrical selection of skin mesh: experimental analysis and numerical optimization - Mehdi Khayami; Aisa Rassoli; Alireza Feizkhah (Scientific Reports)
Abstract Burns are among the most common injuries throughout history, and their treatment varies depending on the severity. Third-degree burns, the most severe and deadly type, cause numerous fatalities worldwide each year but can be treated using the skin mesh grafting technique—one of the latest advancements in burn care. However, an optimal skin mesh geometry has not yet been identified. This study aims to determine the best geometrical design for skin meshes by minimizing average stress, using Abaqus software for numerical analysis and extracting the hyperelastic mechanical properties of skin used in mesh grafts. Hyperelastic properties of healthy and meshed skin were obtained through uniaxial tensile tests, and different geometries were analyzed using Abaqus. The optimal mesh geometry was then determined using genetic algorithms in Abaqus and MATLAB. A rectangular mesh, measuring 1.939 mm in length and 1.698 mm in width, was identified as the best design with an average stress of 0.0757 MPa. These findings have potential applications in clinical burn research, contributing to the development of improved treatment methods.